Strategies to Improve Public Transportation Services for Students of The University of Bengkulu - Zia Felina; Melawaty Agustien; Edi Kadarsa (Eduvest - Journal of Universal Studies, 2025)
The choice of transportation mode is a crucial aspect of student mobility, especially in higher education environments with high levels of activity. Students tend to select transportation modes based on cost, travel time, convenience, accessibility, and safety. However, the high use of private vehicles among students has led to increased traffic congestion and road accidents, as seen in Bengkulu City. On the other hand, the suboptimal quality of public transportation services has contributed to the low interest of students in using public transport. This study aims to analyze the factors influencing the transportation mode choice of Universitas Bengkulu students and to evaluate the effectiveness of public transportation services. The method used is binary logistic regression analysis combined with stated preference to understand mode preferences based on cost and travel time comparisons. The resulting mode choice model indicates that students prefer private vehicles unless public transportation offers more competitive costs and travel times. The study results reveal that travel cost and time are the most influential factors in mode selection. If public transportation becomes more affordable or offers shorter travel times, students are more likely to switch to it. The study concludes that improving the quality of public transportation services, particularly in terms of cost efficiency and punctuality, can increase student interest in using public transport, thereby supporting a more sustainable transportation system.